Eficacy of ivermectin, moxidectin and febendazole in equine in Brazil - Vera, João Henrique Silva [UNESP]; Fachiolli, Daniele Floriano [UNESP]; Ramires, Lívia Magosso [UNESP]; de Lima Saes, Isabela [UNESP]; Yamada, Paulo Henrique [UNESP]; Gonçalves, Juliana Alencar [UNESP]; de Oliveira, Kátia [UNESP]; do Amarante, Alessandro Francisco Talamini [UNESP]; de Soutello, Ricardo Velludo Gomes [UNESP] (Elsevier, 2020)
The objectives of the present study were to evaluate the efficacy of three anthelmintic drugs, i.e. fenbendazole, ivermectin and moxidectin; to determine the genera and species of the most abundant strongyles; and to investigate parasite control measures used in herds of horses in the western region of the state of São Paulo, Brazil. This study was onducted between February and December 2013 on 10 farms in this region. Coprological evaluations were conducted for counting the numbers of eggs per gram of feces (EPG) and coprocultures were made in order to identify third-stage larvae (L3) of strongyles. Parasite control measures were investigated by surveying each farm's management and characteristics. A fecal egg count reduction test (FECRT) was used to determine the anthelmintic efficacy based on EPG count results before and after treatment. The FECRT showed that anthelmintic resistance to fenbendazole was present and that ivermectin and moxidectin had high effectiveness in the western region of the state of São Paulo. Identification of L3 revealed that there was high prevalence of cyathostomins among strongyle larvae. The highest prevalence of Strongylus vulgaris occurred on farms where the intervals between deworming were long. The questionnaire applied showed that ivermectin was the drug most used among these farmers.
Keywords: Anthelmintic resistance; Cyathostomins; Horse; Strongylus